Assessment of the Calorie-Protein Consumption Pattern among Rural and Low-Income Urban Households in Indonesia - Muzayyanah, Mujtahidah Anggriani Ummul Muzayyanah (2015)
The study assessed the calorie-protein consumption pattern from livestock products food among rural and low-income urban households in Indonesia. National household survey data were used in this study, particularly households in DI Yogyakarta Province (here after DIY Province). The data collected were analyzed using descriptive statistics and nutrient (calorieprotein) estimation technique. The results showed that their average monthly expenditure was 1,533,481.38 IDR for the rural and 2,870,942.48IDR for the low-income urban households. Food was almost to be the major item in their consumption-expenditure. Rural household spent 53.6 % of their income for food while low-income urban household spent only 41.4% from their monthly income. The low-income urban households had higher calorie intake than that of the rural household. This situation was not different with the protein consumption pattern. As to the recommended minimum daily calorie-protein intake, households in both areas consumed significantly less than the government recommendation.